Ocena ekonomicznej efektywności inwestycji w energetykę wiatrową - analiza studium przypadku - Ligus, Magdalena (Economic Effectiveness of Wind Energy Project Assessment - the Case Study, 2007)
The study concerns methodical aspects of economic effectiveness of wind energy projects assessment, based on cost-benefit analysis CBA. The differences between financial and economic effectiveness of ecological investment projects, among with renewable energy projects, were provided. The corrections allowing the transfer from financial to economic calculation and the case of wind energy project were presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1159, s. 230-240